2021
DOI: 10.1111/bjd.20584
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of chilblain‐like lesions during the second wave of the COVID‐19 pandemic: a cohort follow‐up

Abstract: Funding sources: W.Y. was supported by the Yen Tjing Ling Medical Foundation.Conflicts of interest: A.P. receives departmental research funding as coinvestigator on a phase II Pfizer-funded clinical trial investigating the use of three kinase inhibitors in the treatment of hidradenitis suppurativa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…As reflected in Figure 1 While investigations to understand the pathophysiology of pandemic-associated pernio continue, [16][17][18][19] furthermore, the temperatures during the third wave were 1-1.5°C lower than mean temperatures from the three previous years.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As reflected in Figure 1 While investigations to understand the pathophysiology of pandemic-associated pernio continue, [16][17][18][19] furthermore, the temperatures during the third wave were 1-1.5°C lower than mean temperatures from the three previous years.…”
Section: Discussionmentioning
confidence: 98%
“…While investigations to understand the pathophysiology of pandemic‐associated pernio continue, 16 , 17 , 18 , 19 evidence has shown that SARS‐CoV‐2 spike protein and robust IFN‐1 response are seen in the skin of patients with chilblains, suggesting an excessive innate immune skin response to SARS‐CoV‐2. These findings suggest IFN‐1 signaling may affect host outcomes to COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, proponents of the association with COVID-19 point to "outbreaks" of chilblain-like lesions corresponding to CO-VID-19 waves and propose that an effi cient, type I interferon-driven antiviral response could induce pernio-like lesions and suppress both symptoms and confi rmatory testing. [25][26][27][28][29] Interestingly, information is accumulating about pernio-like lesions in "long-hauler" patients, with a signifi cant association reported between persistent cutaneous and extracutaneous symptoms. [30][31][32] While the debate continues, if these lesions are truly a COVID-19 manifestation, they are fortunately associated with high survival rates (96.4% 6 to 98.7% 3 ) and few or no systemic symptoms.…”
Section: ■ Pseudo-chilblains: Link To Covid-19 Debatedmentioning
confidence: 99%
“…Une étude plus récente sur 50 malades a détecté par Enzyme-Linked Immunospot (ELISPOT) une réponse IFN gamma sur cellules mononucléées sanguines stimulées in vitro par des protéines virales chez 33 % des patients avec engelures possiblement associées au SARS-CoV-2 mais dans la même proportion chez des contrôles sains, rendant moins probable le schéma COVID et réponse IFN/engelure [ 13 ]. Lors de la 2e vague, en automne, les taux de récidive des engelures étaient supérieurs à 60 % [ [14] , [15] ]. Une équipe a étudié le taux de récidive des engelures et la corrélation géographique avec les cas de COVID dans 23 centres en Californie.…”
Section: Covid Et Peauunclassified